Foreign body stone in oesophagus: a unique case - Sah, B P; Chettri, S T; Prasad, J N.; Gupta, P P; shah, S P; Paudel, D; Jaiswal, R K (Health Renaissance, 2015)
Foreign body ingestion is a common occurrence in children and in specific high-risk groups. It is usually diagnosed based on a history of ingestion given by the patient or an observer. However, children and mentally retarded adults may be unable to give an accurate history, and a high index of suspicion must be maintained in these groups. We report a rare case of foreign body stone in an mentally retarded adult which presented with drooling and impaired feeds, thence enabling for high index for suspicion. Health Renaissance 2014;12(2): pp: 140-142